Creating legitimate authority for environmental governance and new market creation: A case study from Australia. (February 2015) - Knight, Eric; Knox-Hayes, Janelle
New markets and governance arrangements have emerged in recent years to address grand challenges at the interface of science, economics and politics. Whereas much has been written on the technical design on these markets, this paper focuses on how these complex socio-economic systems are created and evolve over time. Drawing on theories of legitimacy, we propose a model for how legitimate authority is created in environmental governance along three bases: scientific authority, economic authority and emotive authority. We distinguish our approach from the literature on power by examining discursive practices that create legitimacy over time. Our analysis relies on the case study of the Australian carbon market and uses in-depth, semi-structured interviews with 45 respondents across multiple fields. Our findings have implications for theory and policy practice.